Application of extracellular vesicles in the diagnosis and treatment of prostate cancer: Implications for clinical practice. (November 2021) - Oey, Oliver; Ghaffari, Mazyar; Li, Jiao Jiao; Hosseini-Beheshti, Elham
Graphical abstract: Highlights: Extracellular vesicles (EV) mediate prostate cancer progression and metastasis. EV have a great potential to be used as liquid biopsy biomarkers in the diagnosis of prostate cancer. EV can be used to guide and personalize treatment decisions in prostate cancer. EV-based prostate cancer tests are becoming increasingly utilized in clinical practice. Abstract: Extracellular vesicles (EV) are cell-derived lipid bilayer-delimited structures providing an important means of intercellular communication. Recent studies have shown that EV, particularly exosomes and large-oncosomes contain miRNA and proteins crucial in prostate cancer (PCa) progression, metastasis and treatment resistance. This includes not just EV released from PCa cells, but also from other cells in the tumor microenvironment. PCa patient derived EV have a unique composition compared to healthy and benign prostatic diseases. As such, EV show promise as diagnostic liquid biopsy biomarkers, both as an adjunct and alternative to the invasive current gold-standard. EV could also be utilized to stratify patients' risk and predict response to hormonal, chemo, immune- and targeted therapy, which will direct future treatment decisions in PCa. We present a summary of the current evidence on the role of EV in PCa and the application of EV in PCa diagnosis and treatment to optimize patient outcomes.